Anatomy of a duchy : the political and ecclesiastical structures of early Přemyslid Bohemia - Kalhous, David, 1978- (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2012)
An analysis of the early Přemyslid realm provides an opportunity for recognizing the importance of different factors involved in the formation of stable social structures in the early medieval regnum. The contemporary narrative emphasizes the importance of violence, where the Přemyslid princes and their powerful retinues imposed princely will on elites and freemen in Bohemia and Moravia. However, our attention also turns to the problematic evidence of assumed powerful cavalry armies and the importance of communication between prince, elites and church, somewhat problematizing the role of violence as the primary tool of governance. Furthermore, an analysis of “otherness” in Saxon chronicles and a comparison of different traditions of St. Wenceslas and Great Moravia confirm the importance of the “Identitätsbildung”-process and “ideology” as stabilising factors in the new Přemyslid regnum.